Investigating the contribution of extended radio sources to the Epoch of Reionization power spectrum. Issue 1 (13th May 2022) - Cook, J H; Trott, C M; Line, J L B
ABSTRACT: We investigate the contribution of extended radio sources such as Centaurus A, and Galactic supernova remnants (SNRs) to our ability to detect the statistical 21-cm signal from the Epoch of Reionisation (EoR) with the Murchison Widefield Array (MWA). These sources are typically ignored because they are in highly attenuated parts of the MWA primary beam, however, in aggregate, these sources have apparent flux densities of 10 Jy on angular scales we expect to detect the 21-cm signal. We create bespoke multicomponent 2D Gaussian models for Galactic SNRs and for Centaurus A, and simulate the visibilities for two MWA snapshot observations. We grid those visibilities and then Fourier transform them with respect to frequency, averaging them both spherically and cylindrically to produce the 1D and 2D power spectra. We compare the simulated 1D power spectra to the expected 21-cm power spectrum. We find that although these extended sources are in highly attenuated parts of the MWA primary beam pattern, collectively they have enough power (∼10 4 −10 5 mK^2 h^-3 Mpc^3 ) on EoR significant modes (|k| 0.1 h Mpc^-1) to prohibit detection of the 21-cm signal (∼10 4 mK^2 h^-3 Mpc^3 ). We find that 50-90 per cent of sources must be removed in order to reduce leakage to a level of 10-20 per cent of the 21-cm power spectrum on EoR significant modes. The effects of wide-field extended sources will have implications on the detectability of the 21-cm signal for the MWA and with the future Square Kilometre Array (SKA).